Papillary Muscle Free Strain in Patients with Severe Degenerative and Functional Mitral Regurgitation - Kılıcgedik, Alev; Kahveci, Gokhan; Gurbuz, Ahmet Seyfeddin; Karabay, Can Yucel; Guler, Ahmet; Efe, Suleyman Cagan; Aung, Soe Moe; Arslantas, Ugur; Demir, Serdar; Izgi, Ibrahim Akin; Kirma, Cevat (Arquivos brasileiros de cardiologia, 2017)
The role of papillary muscle function in severe mitral regurgitation with preserved and reduced left ventricular ejection fraction and the method of choice to evaluate PM have still been the subjects of controversy. To evaluate and compare papillary muscle function in and between patients with severe degenerative and functional mitral regurgitation by using the free strain method. 64 patients with severe mitral regurgitation - 39 patients with degenerative mitral regurgitation (DMR group) and 25 patients with severe functional mitral regurgitation (FMR group) - and 30 control subjects (control group) were included in the study. Papillary muscle function was evaluated through the free strain method from apical four chamber images of the anterolateral papillary muscle (APM) and from apical three chamber images of the posteromedial papillary muscle (PPM). Global left ventricular longitudinal and circumferential strains were evaluated by applying 2D speckle tracking imaging. Global left ventricular longitudinal strain (DMR group, -17 [-14.2/-20]; FMR group, -9 [-7/-10.7]; control group, -20 [-18/-21] p < 0.001), global left ventricular circumferential strain (DMR group, -20 [-14.5/-22.7]; FMR group, -10 [-7/-12]; control group, -23 [-21/-27.5] p < 0.001) and papillary musle strains (PPMS; DMR group, -30.5 [-24/-46.7]; FMR group, -18 [-12/-30]; control group; -43 [-34.5/-39.5] p < 0.001; APMS; DMR group, (-35 [-23.5/-43]; FMR group, -20 [-13.5/-26]; control group, -40 [-32.5/-48] p < 0.001) were significantly different among all groups. APMS and PPMS were highly correlated with LVEF (p < 0.001, p < 0.001; respectively), GLS (p < 0.001, p < 0.001; respectively) and GCS (p < 0.001, p < 0.00; respectively) of LV among all groups. No correlation was found between papillary muscle strains and effective orifice area (EOA) in both groups of severe mitral regurgitation. Measuring papillary muscle longitudinal strain by the free strain method is practical and applicable. Papillary muscle dysfunction plays a small role in severe MR due to degenerative or functional causes and papillary muscle functions in general seems to follow left ventricular function. PPM is the most affected PM in severe mitral regurgitation in both groups of DMR and FMR. O papel da função do músculo papilar na regurgitação mitral grave com fração de ejeção do ventrículo esquerdo preservada e reduzida e o método de escolha para avaliar PM ainda são objetos de controvérsia. Avaliar e comparar a função dos músculos papilares entre pacientes com insuficiência mitral funcional e degenerativa pelo método free strain. 64 pacientes com insuficiência mitral grave - 39 pacientes com insuficiência mitral degenerativa grave (grupo IMD) e 25 com insuficiência mitral funcional grave (grupo IMF) - e 30 indivíduos controle (grupo controle) foram incluídos no estudo. A função dos músculos papilares foi avaliada pelo método free strain a partir de imagens apicais quatro-câmaras do músculo papilar anterolateral (MPA) e imagens apicais três-câmaras do músculo papilar posteromedial (MPP). Strains circunferenciais e longitudinais globais do ventrículo esquerdo foram avaliados por meio de imagens bidimensionais a partir do rastreamento de conjunto de pontos de cinza (speckle tracking). O strain longitudinal global do ventrículo esquerdo (grupo IMD, -17 [-14,2/-20]; grupo IMF, -9 [-7/-10,7]; grupo controle, -20 [-18/-21] p < 0,001); strain circunferencial global do ventrículo esquerdo (grupo IMD, -20 [-14,5/-22,7]; grupo IMF, -10 [-7/-12]; grupo controle, -23 [-21/-27,5] p < 0,001) e strains de músculos papilares (MPP; grupo IMD, -30,5 [-24/-46,7]; grupo IMF, -18 [-12/-30]; grupo controle; -43 [-34,5/-39,5] p < 0,001; MPA; grupo IMD, (-35 [-23,5/-43]; grupo IMF, -20 [-13,5/-26]; grupo controle, -40 [-32,5/-48] p < 0,001) mostraram-se significativamente diferentes nos grupos. MPA e MPP mostraram-se altamente correlacionados com a FEVE (p < 0,001, p < 0,00; respectivamente), SLG (p < 0,001, p < 0,001; respectivamente) e SCG (p < 0,001, p < 0,001; respectivamente) do VE entre todos os grupos. Não foi encontrada correlação entre os strains de músculos papilares e área eficaz do orifício (AEO) nos grupos de insuficiência mitral grave. A medição do strain longitudinal de músculos papilares pelo método free strain é prática e aplicável. A disfunção dos músculos papilares tem um papel pequeno em IM grave devido a causas degenerativas e funcionais, e a função dos músculos papilares, em general, parece seguir a função ventricular esquerda. O MPP é o MP mais afetado na insuficiência mitral em ambos os grupos, IMD e IMF.